Development of an Electrical Monitoring and Control System Using a Google Assistant-Based Smart Plug - Hasanuddin, M. Hasanuddin; Justam; Batari Tammaka, Arifah (Bahasa Indonesia, 2025)
The increasing electricity consumption in the household sector impacts energy efficiency and quality. This research develops an Internet of Things (IoT)-based smart plug to monitor current and voltage, control power via Google Assistant, and detect power outages. The system utilizes current and voltage sensors that transmit data to a dashboard via Blynk Cloud, with an ESP32 microcontroller as the main hub. Power control is performed through Google Assistant and the Blynk dashboard, while power outage notifications are sent via email based on relay voltage values. Test results show that the system accurately monitors current and voltage, including during smartphone battery charging. Power control via the Blynk application has an average delay of 0.18 seconds, whereas control via Google Assistant shows an average delay of 3.4 seconds for activation and 5.26 seconds for deactivation. The system also successfully detects power outages and sends real-time notifications. With these features, the smart plug enhances the efficiency and intelligent management of household electricity consumption.